Association of erectile dysfunction and peripheral arterial disease in NHANES 2001-2004: a cross-sectional study - Wang, Ganggang; Ni, Caifang (Frontiers in Endocrinology, 2024)
To evaluate the association between Erectile dysfunction (ED) and peripheral arterial disease (PAD) in adult American males using a large database.The relationship between ED and PAD prevalence among participants in the 2001-2004 National Health and Nutrition Examination Survey (NHANES) database was assessed using a series of statistical analyses. ED was evaluated based on a single-item measure of self-reported erection problems from the Massachusetts Male Aging Study. PAD was defined as ankle-brachial index (ABI) < 0.9 in at least one leg.Multifactorial logistic regression models were used to investigate the association between ED and PAD.A total of 2394 participants were enrolled, of whom 905 individuals (37.8%) were diagnosed with ED. After adjusting for confounding variables, the association between ED and PAD remained positive, with an odds ratio of 2.05 (95% confidence interval 1.24-3.39). Subgroup analysis revealed that the relationship between ED and PAD was significant in patients aged >50 years old, without hypertension, without diabetes, without cardiovascular disease, without high cholesterol, former smokers, low physical activity levels, and a body mass index of 25-30 (P < 0.05). In addition, all subgroups analyzed were evaluated for any potential interaction, and no statistically significant association was discovered.In a sample of US adults aged ≥40, this cross-sectional study found that ED is related to a higher occurrence of PAD. ED may be an independent predictor of PAD, and thus it should be considered in the treatment of patients with ED.